2006
DOI: 10.2174/092986706779026192
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Therapeutic Strategies for Lung Cancer: Targeting the Cholinergic System

Abstract: One of the earliest descriptions of non-neuronal ACh synthesis was by Morris who reported that ACh was synthesized in the placenta [1]; furthermore, Falugi et al. showed the presence of AChE in human fibrosarcoma cells [2]. Afterward, the expression of ACh, AChE, and cholinergic receptors in non-neuronal cells was reported in several studies [3-16]. Indeed, recent data reported that SCLC expresses a cholinergic autocrine loop that can regulate cell growth. Such work demonstrates that SCLC cells have a choliner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 121 publications
(194 reference statements)
2
49
0
Order By: Relevance
“…16 The animal venom toxins antagonists of AChR [i.e., bungarotoxin (BTX) from the Bungarus multicinctus snake and conotoxins purified from the venom of Conus marine snails] have previously been used as molecular tools for the characterization of neuronal nAChR in SCLC, NSCLC and mesothelioma or for inhibiting nicotine action. A latest study 35 showed that a-BTX inhibits the proliferation of human bronchial BEP2D cells exposed to NNK This work is devoted to the memory of Dr. Andr e M enez, President of the French Natural History Museum, and a world-renowned expert in the molecular and structural biology of animal toxins.…”
Section: Uiccmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The animal venom toxins antagonists of AChR [i.e., bungarotoxin (BTX) from the Bungarus multicinctus snake and conotoxins purified from the venom of Conus marine snails] have previously been used as molecular tools for the characterization of neuronal nAChR in SCLC, NSCLC and mesothelioma or for inhibiting nicotine action. A latest study 35 showed that a-BTX inhibits the proliferation of human bronchial BEP2D cells exposed to NNK This work is devoted to the memory of Dr. Andr e M enez, President of the French Natural History Museum, and a world-renowned expert in the molecular and structural biology of animal toxins.…”
Section: Uiccmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] The primary functions of non-neuronal ACh might involve it in cell-to-cell communication mediated by intracellular ion dynamics, linked to the regulation of a number of events, such as cell motility, responses to the cellular environment and apoptosis. 6,[16][17][18][19][20] Moreover, the discovery of functional acetylcholine receptors (AChR) on lung epithelial cells and lung tumors raises the question of whether exposure to nicotine could also participate in lung cancer pathogenesis by activating signal transduction pathways, such as the Akt pathway, and/or overcome apoptotic responses engendered by carcinogen exposure. [16][17][18][19][20] It has been largely demonstrated that nicotine stimulates the proliferation of human small cell lung cancer (SCLC) cells by binding the a7-nicotinic acetylcholine receptors (nAChR), resulting in the release of 5-HT.…”
Section: Uiccmentioning
confidence: 99%
“…Moreover, it has been recently reported that nicotine potently induces Bad phosphorylation through linkage with a nicotinic acetylcholine receptor subunit, α7-nAChR (Chna7). Chna7 is involved in the regulation of cell proliferation or apoptosis in the lung (Dasgupta et al, 2006;Jin et al, 2004;Russo et al, 2006;Schuller et al, 2000). Bad is a pro-apoptotic factor, but phosphorylation of Bad has been demonstrated to inactivate its pro-apoptotic function.…”
Section: Discussionmentioning
confidence: 99%
“…nAChR are acetylcholine gated ion channels consisting of homo-or heteropentamers subunits arranged symmetrically around a membrane perpendicular axis, outlining the ionic hole (Russo et al, 2006;Taly et al, 2009) (Fig. 2.).…”
Section: Neurochemistry Of Nicotinic Receptor (Nachr)mentioning
confidence: 99%
“…The homomeric 7 nAChR is a special case, since having five agonist-binding sites per receptor can bind from two to five molecules of agonist. 7-nAChR utilizes multiple calcium amplification pathways to efficiently raise the intracellular calcium levels by subsequent activation of voltage-gated calcium channels as well as calcium release from the endoplasmic reticulum (Russo et al, 2006;Taly et al, 2009). …”
Section: Neurochemistry Of Nicotinic Receptor (Nachr)mentioning
confidence: 99%